Association between diet quality and sleep apnea in the Multi-Ethnic Study of Atherosclerosis. Issue 1 (22nd October 2018) - Reid, Michelle; Maras, Janice E; Shea, Steven; Wood, Alexis C; Castro-Diehl, Cecilia; Johnson, Dayna A; Huang, Tianyi; Jacobs, David R; Crawford, Allison; St-Onge, Marie-Pierre; Redline, Susan
Abstract: Rationale: Although short sleep duration has been linked to unhealthy dietary patterns, little is known about the association of obstructive sleep apnea (OSA), a disorder characterized by sleep fragmentation and diet. Study Objectives: Investigate associations between diet quality and OSA in the Multi-Ethnic Study of Atherosclerosis and assess whether reductions in slow-wave sleep (stage N3) and rapid eye movement (REM) sleep are potential mediators for these associations. Methods: A diverse population ( N = 1813) completed a food frequency questionnaire and underwent Type 2 in-home polysomnography, which included measurement of N3 and REM sleep and apnea–hypopnea index (AHI). Moderate-to-more severe OSA was defined as having an AHI > 15 events/hr. Results: Participants were 53.9% female with a mean age of 68.3 ( SD 9.1) years. Approximately 33.8% were categorized as having moderate-to-more severe OSA. In adjusted analyses, OSA was associated with lower intakes of whole grains, (β = −0.200, SE = 0.072, p < 0.01), higher intakes of red/processed meat, (β = −0.440, SE = 0.136, p < 0.01), and lower overall diet quality (β = −1.286, SE = 0.535, p = 0.02). Stage N3 sleep partially explained the associations between red/processed meat and overall diet quality score with OSA. Conclusions: Moderate-to-more severe OSA is associated with a less healthy dietary profile that is partially explained by reduced N3 sleep. These findings suggest the opportunity to target sleep quality in interventions aimed at improving cardio-metabolic risk factors in patients with OSA.